Staphylococcus aureus adaptation to aerobic low-redox-potential environments: implications for an intracellular lifestyle. Issue 7 (17th May 2019) - Christmas, Benjamin A. F.; Rolfe, Matthew D.; Rose, Matthew; Green, Jeffrey
Abstract : Methicillin-resistant Staphylococcus aureus is a 'superbug' that is responsible for extensive death and morbidity. Chronic S. aureus infections are associated with the presence of intracellular bacteria and the host cytosol is an aerobic low-redox-potential (Eh ) environment. How S. aureus adapts to aerobic low-Eh environments is understudied. A low external Eh, imposed by the non-metabolizable reductant dithiothreitol, resulted in transcriptional reprogramming mediated by the redox-responsive transcription factors AgrA, Rex and SrrBA, resulting in a shift towards fermentative metabolism. Accordingly, in the presence of the host cytoplasmic reductant glutathione, the aerobic respiration of S. aureus was impaired, the intracellular NADH:NAD + ratio increased, lactate dehydrogenase was induced, resistance to the aminoglycoside antibiotic gentamicin was enhanced and greater numbers of small-colony variants (SCVs) were detected. These observations suggest that entry of S. aureus into the aerobic low-Eh environment of the host cytosol could result in adaptive responses that promote the formation of SCVs.